2010
DOI: 10.1094/pdis-94-4-0478c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Rust of Blueberry Caused by Thekopsora minima on Vaccinium corymbosum in the Western Cape, South Africa

Abstract: Southern highbush blueberry plants (Vaccinium corymbosum interspecific hybrids) showing rust-like symptoms were observed in July 2006 in Porterville in the Western Cape (WC), South Africa. Diseased plants were also found in Villiersdorp and George in the WC in 2007. In 2008, symptoms were observed in George, and in 2009, in all the previous reported areas. Cvs. Bluecrisp, Emerald, Jewel, Sharpblue, and Star were infected. Reddish-to-brown spots appeared on the adaxial surface of leaves and developed into yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Urediniospores developed on the lower surface of older leaves as yellow-orange pustules within 10 to 14 d of infection and abundant sporulation across the lower leaf surface was observed. The disease symptoms displayed by these accessions were similar to the ones described in previous leaf rust reports (Barrau et al, 2002;Dal Bello and Perello, 1998;Keith et al, 2008;McTaggart et al, 2013;Mostert et al, 2010;Rebollar-Alviter et al, 2011;Shands et al, 2018;Wiseman et al, 2016;Zheng et al, 2017).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Urediniospores developed on the lower surface of older leaves as yellow-orange pustules within 10 to 14 d of infection and abundant sporulation across the lower leaf surface was observed. The disease symptoms displayed by these accessions were similar to the ones described in previous leaf rust reports (Barrau et al, 2002;Dal Bello and Perello, 1998;Keith et al, 2008;McTaggart et al, 2013;Mostert et al, 2010;Rebollar-Alviter et al, 2011;Shands et al, 2018;Wiseman et al, 2016;Zheng et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…The incidence of the disease has been increasing in the United States, where the pathogen has been reported in several states, including Delaware, New York, Michigan, Oregon, Hawaii, California, and Georgia (Keith et al, 2008;Sato et al, 1993;Shands et al, 2018;Wiseman et al, 2016). In addition, leaf rust has been reported in many countries, including South Africa, Mexico, Spain, Argentina, Australia, and China (Barrau et al, 2002;Dal Bello and Perello, 1998;McTaggart et al, 2013;Mostert et al, 2010;Rebollar-Alviter et al, 2011;Zheng et al, 2017). T. minima is a heteroecious fungus requiring both primary and alternate host plants to complete its life cycle (Hiratsuka 1965).…”
mentioning
confidence: 99%
“…Thekopsora minima was recently reported from South Africa (Mostert et al 2010) and Mexico (Rebollar-Alviter et al 2011) based on inoculation studies and molecular data. Australian specimens of blueberry rust held in BRIP were identified as T. minima by morphology, and in some cases by LSU sequence data, which is indicated by GenBank numbers as follows.…”
mentioning
confidence: 87%
“…Although few blueberry diseases have been observed in South Africa, there is little studied or published in the country. The only scientific published report is on leaf rust on blueberries observed in the Western Cape Province during 2006–2009 by Mostert et al (2010), which identified Thekopsora minima as the causal agent. Over the past few years, the diagnostic service at the Agricultural Research Council (ARC), Biosystematics Division, Mycology Unit, has received numerous blueberry samples from various growers in South Africa requesting identification of the cause of damage to their plants.…”
Section: Introductionmentioning
confidence: 99%